The Interaction of Tax Exemptions and Individual Tax Reform Preferences - Salvatore Barbaro; Jens Südekum (Institute for the Study of Labor (IZA), 2005)
The individual voting behavior on the abolishment of single income-tax exemptions crucially depends on how strongly agents are affected by other deduction possibilities that are not at stake in the reform plans of the government. The interactions depend (i) on the shape of the tax schedule, and (ii) on how the government wants to use the revenue that is generated by the cut of tax privileges. If government plans to increase redistribution in form of lump-sum transfers, then the political chances of a tax reform increase with the existence of other deduction possibilities under progressive taxation. With proportional taxation and a budgetenlargement policy, the voting decision depends only on the particular tax privileges at stake. Matters are different if the government wants to adopt a revenue-neutral tax-cut-cum-basebroadening policy. Except for strong progression, it is less likely that an agent supports the elimination of tax privileges the stronger she is affected by other exemptions in the back.
Keywords: D72; D74; 330; income tax reform; public choice